2018
DOI: 10.2147/cmar.s176833
|View full text |Cite
|
Sign up to set email alerts
|

CCNA2 acts as a novel biomarker in regulating the growth and apoptosis of colorectal cancer

Abstract: ObjectiveColorectal cancer (CRC) is considered to be the most prevalent malignant tumors that contribute to high cancer-related mortality. However, the signaling pathways involved in CRC and CRC-driven genes are largely unknown. We seek to discover a novel biomarker in CRC.Materials and methodsAll clinical CRC samples (n=33) were from Xiangya Hospital. We first selected CCNA2 by integrated bioinformatics analysis of four GSE databases. Next, the expression of CCNA2 in tissues and cell lines was verified by qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 57 publications
6
67
0
Order By: Relevance
“…37 CCNA2 was shown to act as a oncogene and played a crucial role in regulating cancer cell growth and apoptosis, serving as a new biomarker for the diagnosis and therapy of CRC. 38,39 These findings support the potential of URB1 and CCNA2 as a linkage of crosstalk between mTORC1 and p53/ p21 signaling. Thus, it is reasonable to propose that the essential mTORC1/RAPTOR-URB1-CCNA2 axis plays a role in tumorigenesis.…”
Section: F I G U R Esupporting
confidence: 58%
“…37 CCNA2 was shown to act as a oncogene and played a crucial role in regulating cancer cell growth and apoptosis, serving as a new biomarker for the diagnosis and therapy of CRC. 38,39 These findings support the potential of URB1 and CCNA2 as a linkage of crosstalk between mTORC1 and p53/ p21 signaling. Thus, it is reasonable to propose that the essential mTORC1/RAPTOR-URB1-CCNA2 axis plays a role in tumorigenesis.…”
Section: F I G U R Esupporting
confidence: 58%
“…We searched the literature in PubMed for associations among the twenty hub genes in CRC. In Yanqi Gan et al's study, they revealed that expression of CCNA2 in CRC tissues is higher than that in normal tissues and that CCNA2 knockdown could significantly suppress CRC cell growth by impairing cell cycle progression and inducing cell apoptosis (Gan et al, 2018). TOP2A is a gene that involves copy number variations and chromosomal instability in many cancers (Simon et al, 2002;Bofin et al, 2003;Chen et al, 2015;Sonderstrup et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of liver cancer, researchers found that ZHX2 can repress CCNA2 transcription by binding the promoter regions of CCNA2, thereby inhibiting the proliferation of hepatoma cells [25]. Ya qi Gan et al found the expression of CCNA2 was higher in colorectal cancer than the normal colorectum, and reducing the expression of CCNA2 could influence cell cycle, inhibit the proliferation of tumor cells and increase apoptosis [26]. Francesca et al showed that miR-10b may affect tumor cell proliferation and invasion by acting on CCNA2 in breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%